La Culture Nationale Et L’intégration Relationnelle Des Supply Chains : Etude Qualitative Sur Les Dimensions De La Culture Marocaine Selon Le Modèle De Geert Hofstede - Hicham, M. Hamri Mohammed; Ouafae, Zerouali Ouariti; Hafsa, Lechheb (European Scientific Journal, ESJ, 2016)
The relational integration of Supply Chains has provoked a number of rich debates, indicating its importance and relevance for firms seeking performance and gaining significant market share. However, relational integration of Supply Chains refers to the integration of several management modes, and several national cultures. Therefore, the aim of this paper is to study the dimensions of the Moroccan culture, through a qualitative study, in order to give an answer to this research problem: Does the Moroccan culture present determinants favorable to the relational integration Supply Chains?